Identification of possible natural compounds as potential inhibitors against Plasmodium M1 alanyl aminopeptidase - Soliman, Omar Samir Abdel Ghaffar (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2019)
Malaria is a major tropical health problem with a 29% mortality rate among people of all ages; it also affects 35% of the children. Despite the decrease in mortality rate in recent years, malaria still results in around 2000 deaths per day. Malaria is caused by Plasmodium parasites and is transmitted to humans via the bites from infected female Anopheles mosquitoes during blood meals. There are five different Plasmodium species that can cause human malaria, which include Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, Plasmodium ovale and Plasmodium knowlesi. Among these five species, the most pathogenic ones are Plasmodium falciparum and Plasmodium vivax. Malaria is usually hard to diagnose because the symptoms are not exclusive to malaria and very similar to flu, e.g., fever, muscle pain, and chills, which lead to the misdiagnosis of malaria cases. Malaria is lethal if not treated because it can cause severe complications in the respiratory tract, liver, metabolic acidosis, and hypoglycemia. The malaria parasite life cycle includes two types of hosts, i.e., a human host and female Anopheles mosquito host. Malaria continuously develops resistance to the available drugs, which is one of the major challenges in disease control. This situation confirms the need to develop new drugs that target virulence factors of malaria. The malarial parasite has three main life cycle stages, which include the host liver stage, host blood stage and vector stage. In the blood stage, parasites degrade hemoglobin to amino acids, which is important as these parasites cannot produce their own amino acids. Different proteases are involved in this hemoglobin degradation process. M1 alanyl aminopeptidase is one of these proteases involved at the end of hemoglobin degradation. This study focused on M1 alanyl aminopeptidase as a potential drug target. M1 alanyl aminopeptidase consists of four domains: N-terminal domain, catalytic domain, middle domain and C-terminal domain. The catalytic domain remains conserved among different Plasmodium species. Inhibition of this enzyme might prevent Plasmodium growth as it can't produce its own amino acids. In this study, sequence analysis was carried out in both human and Plasmodium M1 alanyl aminopeptidase to identify conserved and divergent regions between them. 3D protein models of the M1 alanyl aminopeptidase from Plasmodium species were built and validated. Then the generated models were used for virtual screening against 623 compounds retrieved from the South African Natural Compounds Database (SANCDB, https://sancdb.rubi.ru.ac.za/). Virtual screening was done using blind and targeted docking methods. Docking was used to identify compounds with selective high binding affinity to the active site of the parasite protein. In this study, one SANCDB compound was selected for each protein: SANC00531 was selected against P. falciparum M1 alanyl aminopeptidase, SANC00469 against P. knowlesi, SANC00660 against P. vivax, SANC00144 against P. ovale and SANC00109 against P. malariae. It was found that Plamsodium M1 alanyl aminopeptidase can be used as a potential drug target as it showed selective binding against different inhibitor compounds. This result will be investigated in future work though molecular dynamic analysis to investigate the stability of protein-ligand complexes.
Keywords: Plasmodium; Malaria -- Chemotherapy; Plasmodium -- Inhibitors; Drug resistance in microorganisms; Aminopeptidases